SISTEM EKONOMI ISLAM: SUATU PENDEKATAN FILSAFAT, NILAI-NILAI DASAR, DAN INSTRUMENTAL - Abbas, Anwar (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2012)
Islamic economical system has its’ own system. It is not a combination between capitalism and sosialism. Islamic economicalsystem did not put human as a central (anthroposentrism) but as a God servant (âbid) that should serve and carry out the tasks entrusted to the servant (khalîfah). Therefore, the economic practice must uphold the values of ownership, the values of justice, freedom, balance, and in accordance with the fraternity and togetherness guided by religious teachings in order to create good personal living arrangements, social and nationalDOI: 10.15408/aiq.v4i1.2542